Transthyretin-assoziierte familiäre Amyloidpolyneuropathie - Niemietz, Christoph; Röcken, Christoph; Schilling, Matthias; Stypmann, Jörg; Uhlig, Constantin E.; Schmidt, Hartmut H.-J. (DMW - Deutsche Medizinische Wochenschrift, 2018)
Transthyretin-related Familial Amyloid Polyneuropathy (ATTR Amyloidosis, former FAP, here called TTR-FAP) is a rare, progressive autosomal dominant inherited amyloid disease ending fatal within 5 – 15 years after final diagnosis. TTR-FAP is caused by mutations of transthyretin (TTR), which forms amyloid fibrils affecting peripheral and autonomic nerves, the heart and other organs. Due to the phenotypic heterogeneity and partly not specific enough clinical symptoms, diagnosis of TTR-FAP can be complicated. False diagnoses can include idiopathic polyneuropathy, chronic inflammatory demyelinating polyneuropathy, diabetic neuropathy as well as paraneoplastic syndrome. Hence, it is assumed that many cases remain unreported. Early and correct diagnosis of TTR-FAP is crucial, since appropriate therapeutic options exist. TTR-FAP should always be differentially diagnosed, when apart from a progressive peripheral polyneuropathy, additional symptoms as autonomic dysfunction, cardiomyopathy, gastrointestinal disorders, unexpected loss of weight, carpal tunnel syndrome, restrictions of renal function, epileptic fits, and corneal and vitreous body clouding occur. Histological evidence of amyloid and successive immunohistochemical evidence of transthyretin as well as genetic testing for transthyretin mutations, lead to an accurate diagnosis.
Keywords: Transthyretin; Amyloidose; Polyneuropathie; therapeutische Oligonukleotide; Leber